Review of Rob van der Bliek, ed. 2001. The Thelonious Monk Reader. New York: Oxford University Press - Priestley, Brian (Current Musicology, 2001)
The music of Thelonious Monk has evoked increasing interest in the twenty years since his death. His themes, which used to be thought unappetizing for others to play, are now eagerly lapped up by performance students, as well as by those professionals for whom honoring “the tradition” is an important activity. Already since the 1960s, when the concept of avant-garde jazz meant so many different things to different people, Monk’s combination of surface irregularity with a ruthless inner logic has been consistently influential; in particular, the organic and unstilted use of motivic development in his themes is widely seen as an ideal to aspire to. Meanwhile, his own documentation of these themes-both the original recordings dating principally from 1947-56 and the later extended versions representing his live performance methods-have been remastered and reissued in great profusion. It is understandable that, especially among those absorbed in the music, and among those less captivated by it too, there is also still considerable curiosity about Monk’s history. The Thelonious Monk Reader, a collection of previously published journalism and criticism, usefully focuses on a life of marked contrasts, as far as his public reputation and visibility were concerned, but one balanced by a private existence that was seemingly more stable and unruffled than that enjoyed by most jazz musicians.